Exploring exercise, physical wellbeing and the role of physiotherapy: perspectives from people with narcolepsy - Tadrous, Ragy; O'Rourke, Deirdre; Murphy, Niamh; Quinn, Gillian; Quinn, Caitriona; Slattery, Lisa; Broderick, Julie (Journal of sleep research, 2024)
Summary Narcolepsy is associated with reduced quality of life and physical performance. The study aimed to explore the attitudes of people with Type 1 narcolepsy towards exercise and physical activity, their physical wellbeing, and the potential role of physiotherapy. Semi‐structured interviews were conducted with 22 people with narcolepsy attending a dedicated outpatient narcolepsy clinic located in Dublin, Ireland. Transcripts were iteratively coded; a thematic analysis was undertaken, and key themes were identified. Four themes were identified: ‘Barriers and Facilitators to Exercising’, ‘Social Concerns’, ‘Health Concerns’ and ‘Suggestions for the Role of Physiotherapy’. Future research should explore the potential role of exercise to help manage narcolepsy‐related symptoms in this population.